General Overview of the Causative Agents of Foodborne Illness - Ronald H. Schmidt; Renée M. Goodrich; Douglas L. Archer; Keith R. Schneider (EDIS, 2003)
This is one in a series of facts sheets targeting the retail and processing sector of food safety. This document is FSHN033, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: February 2003.